O impacto da simpatectomia torácica alta percutânea por radiofrequência na qualidade de vida de indivíduos com hiperidrose palmar - Romero, Flávio Ramalho [UNESP] (2015)
INTRODUCTION. Primary hyperhidrosis is a condition with excessive symmetric and bilateral body sweat, without relationship with organic heat lost. It is associated with high negative impact in life quality, interfering in usual activities, labor conditions, social interaction, creating emotional disturbances e psychological problems. The aim of this study was evaluated the impact of high thoracic percutaneous sympathectomy among patients with palmar hyperhidrosis. METHOD. Third-six palmar hyperhidrosis patients were selected for a prospective observational study. They were treated with thoracic sympathectomy in T3 and T4 ganglions by a percutaneous technic using conventional radiofrequency devices. Severity hyperhidrosis scale (HDSS) and quality of life scales were applied (DLQI, Keller and de Campos) preoperatively, in the 1st postoperative day, and in 30th, 90th, 180th and 360th postoperative days. Also, compensatory hyperhidrosis scales (HDSSc and SBCT) were used in the same moments to evaluate the rate and frequency of this complication. RESULTS. All quality of life scales and severity scale evaluation showed statistic significance improves in its results. HDSS preoperative value was 3.64, turned to 1.00 in the 1st PO, keeping in 1.00 in 30th PO, changing to 1.08 in 90th, 1.61 in 180th PO and 1.64 in 360th PO. DLQI scale showed preoperative median value of 39.58, decreasing to 10.58 in 1st PO, 10.56 in 30th PO, 11.83 in 90th PO, 12.75 in 180th PO and 13.17 in 360th PO. Keller scale preoperative values were 101.42, decreasing to 38.28 in the 1st PO, 38.78 in 30th PO, 43.14 in 90th PO, 43.33 in 180th PO and 45.69 in 360th PO. Ribas scale showed preoperative values of 83.94, decreasing to 24.61 in the 1st PO, 25.14 in 30th PO, 31.28 in 90th PO, 32.97 in 180th PO and 33.94 in 360th PO. Palmar temperature evaluation showed significant statistical decreasing of its values, changing of 34.09°C to 31.83°C in 1st PO, and 33.30°C in 360st ...